(untitled) (Desenvolvimento em Questão, 2026)
This study analyzed and compared the economic risks of conventional and organic milk production systems in the regions of São José do Rio Preto, Mococa, and Ribeirão Preto (SP), from January 2017 to September 2021, focusing on the probability of negative net margins. For conventional systems, panel data (typical farms) were used, while a case-study approach was adopted for organic systems. Costs were classified into Effective Operating Cost (EOC) and Total Operating Cost (TOC), and revenues included milk and animal sales, which together composed Gross Revenue (GR). Total Net Margin (TNM) and Net Margin considering only milk sales (MNM) were estimated using stochastic simulations to assess risk. Results indicated a low probability of negative profitability when total GR was included. However, when only milk revenue was analyzed, high liquidity risks emerged, particularly for organic farms, with up to an 87.7% probability that milk revenue would not cover TOC. Despite presenting better zootechnical performance indicators, organic systems showed greater economic vulnerability, mainly due to high expenditures on externally purchased concentrates. Sensitivity analysis revealed that milk revenue and concentrate feed costs were the primary determinants of Net Margin. The findings support management strategies and policy design aimed at strengthening the economic sustainability of dairy farming by highlighting the central role of feed cost control and productive efficiency in mitigating liquidity and profitability risks.